A new species of shrimp, genus Ambidexter Manning & Chace, 1971 (Decapoda: Processidae), from southeastern Caribbean Sea, Venezuela, with key to genus - Rodríguez, Pedro; Lira, Carlos (Zootaxa, 2022)
A new species of processid shrimp, Ambidexter cochensis sp. nov. is described from Venezuela, on the basis of several specimens collected in seagrass beds at a depth less than 1 m. This new species is closely related to A. swifti Abele, 1972 from eastern Pacific, which mainly differs by the number of carpal articles of the second pereiopod, the setation pattern on the telson and the structure of the appendix masculina of the male second pleopod. A key to genus is presented.